(untitled) (Global Journal of Science Frontier Research, 2015)
Bangladesh is one of the most vulnerable countries to climate change with a very high population density. The increasing risks from climate change, sea level rise, and natural and man-made hazards-such as cyclones, storm surge, flooding, land erosion, water logging, and salinity intrusion in soil and water have already adversely affected livelihoods of people living in environmentally fragile coastal areas of Bangladesh. This study identifies the relationship between the characteristics of the farmers and their perception of climate change effects on coastal agriculture at Patuakhali district of Bangladesh. To make the outcomes useful, both qualitative and quantitative approaches of field investigations were done.